2018
DOI: 10.1111/jcmm.13886
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of XPO1 enhances cell death induced by ABT‐199 in acute myeloid leukaemia via Mcl‐1

Abstract: The antiapoptotic Bcl‐2 family proteins play critical roles in resistance to chemotherapy in acute myeloid leukaemia (AML). The Bcl‐2‐selective inhibitor ABT‐199 (Venetoclax) shows promising antileukaemic activity against AML, though Mcl‐1 limits its antileukaemic activity. XPO1 is a nuclear exporter overexpressed in AML cells and its inhibition decreases Mcl‐1 levels in cancer cells. Thus, we hypothesized that the XPO1‐selective inhibitor KPT‐330 (Selinexor) can synergize with ABT‐199 to induce apoptosis in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 55 publications
4
33
0
Order By: Relevance
“…Co-immunoprecipitation revealed that midostaurin treatment reduced Mcl-1 binding to Bim, but increased Bim binding to Bcl-2, in both MOLM-13 and MV4-11 cells. Consistent with our published work (10,11,28), venetoclax treatment reduced Bcl-2 binding to Bim, but increased binding of Mcl-1 to Bim (Figure 3C). In the combined treatment, both Mcl-1 and Bcl-2 binding to Bim were reduced.…”
Section: Midostaurin Downregulates Mcl-1 Expressionsupporting
confidence: 92%
“…Co-immunoprecipitation revealed that midostaurin treatment reduced Mcl-1 binding to Bim, but increased Bim binding to Bcl-2, in both MOLM-13 and MV4-11 cells. Consistent with our published work (10,11,28), venetoclax treatment reduced Bcl-2 binding to Bim, but increased binding of Mcl-1 to Bim (Figure 3C). In the combined treatment, both Mcl-1 and Bcl-2 binding to Bim were reduced.…”
Section: Midostaurin Downregulates Mcl-1 Expressionsupporting
confidence: 92%
“…Venetoclax treatment reduces the interaction of the proapoptotic protein Bim with BCL-2, however the interaction of Bim with the antiapoptotic protein Mcl-1 is thought to mediate resistance to venetoclax [ 57 ]. Treatment with selinexor reduces the levels of Mcl-1, and shows a synergistic effect when combined with venetoclax in AML cells [ 58 ].…”
Section: Preclinical Trials Combining Sines With Conventional Treatmementioning
confidence: 99%
“…Here, we introduce several combinations that can reduce the MCL-1 level indirectly to circumvent the resistance. Indirect MCL-1 inhibitors include the following compounds: bromodomain extra-terminal protein inhibitors (BETis), which reduce MCL-1 and BCL-XL levels while increasing BIM levels and enhance the lethal effects of venetoclax on AML ( 97 ); cyclin-dependent kinase 9 (CDK9) inhibitors, which inhibit the transcription of MCL-1 ( 98 ); midostaurin or gilteritinib, FLT3 inhibitors that induce downregulation of MCL-1 to increase venetoclax activity ( 99 ); CUDC-907, a dual PI3K and histone deacetylase inhibitor that downregulates MCL-1, upregulates BIM, and induces DNA damage ( 100 ); MEK inhibitors ( 101 ); MDM2 inhibitors ( 102 ); PI3K inhibitors ( 103 ); and selinexor, an XPO1-selective inhibitor ( 104 ). In addition, an inhibitor of the Nedd8-activating enzyme (MLN4924) can upregulate Noxa, and 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR) inhibitors (statins) can upregulate PUMA.…”
Section: Venetoclax Resistance and Combination Strategies To Overcomementioning
confidence: 99%